Differentiation of root canal morphology – a review of the literature - Przesmycka, Agata; Tomczyk, Jacek (Anthropological Review, 2016)
The morphological diversity of the inner anatomy of root canals in human permanent teeth is an issue mainly described in endodontics research. In recent years, it is a relatively new point in anthropological studies because it varies by sex, geographic and ethnic circumstances. An unusual number of root canals or their specific systems can differentiate populations around the world. The multiplicity of available methods for detecting root canal systems helps to better understand their complexity; however, most cannot be applied to anthropology due to limitations that occur in the bioarcheological material. Thorough knowledge of the heterogeneity and internal anatomy of the root canals supplies numerous classification systems proposed and improved over the years by many authors. A limited number of studies in the anthropological literature and future research will shed light onto the internal tooth morphology in historical populations. The aim of this paper is to describe various classification systems of root canals applied in endodontics. However, due to the often poor state of preservation and damage of archaeological derived remains, it seems that the best method is the approach that is the simplest and least complicated.